The Impacts of Effective Supply Chain Management Practices and Banking Progress on Economic Growth in Southeast Asian Countries - Tran, Huy Hoang; Nguyen, Hong Anh Thi (International Journal of Supply Chain Management, 2020)
The paper uses the GLS methodology to determine the correlation between supply chain practices, banking progress, and economic growth in Southeast Asian countries (except Singapore) on the author group database obtained from the World Data Progress Indicator (WDI) of the World Bank (WB) in the period 1998 - 2016. The results show that the increase in banking progress causes negative effects on economic growth while effective supply chain practices positively linked with economic growth. An imbalance between progress in the banking sector and the country’s economic growth can lead to negative effects.